Pandangan Masyarakat Terhadap Maraknya LGBT di Era Globalisasi - Dwi Agiyanti; Muhammad Zaki Fadhilan Burhanudin; Nanda Reisya Violetta; Rai Thoriq Azhar; Rakha Farrasya Nurzaky; Supriyono Supriyono (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
In the era of globalization, the views of Indonesian people towards the rise of the LGBT phenomenon have become complex, considering that Indonesia is thick with religious and cultural values. Although the country adheres to human rights principles, an understanding of religious norms is often a filter for views on sexual diversity. Especially among the younger generation, there is significant disagreement on whether the rise of LGBT is in accordance with the ideals of Pancasila as the basis of the state. On the one hand, there are groups that support LGBT rights as a form of respect for human rights, while on the other hand, there are concerns that this phenomenon is not in line with the values of Pancasila which emphasizes unity and unity in diversity. Further research needs to be done to understand more deeply how the views of Indonesian people, especially the younger generation, towards the LGBT phenomenon in the context of the globalization era. The purpose of this study is to examine more deeply and describe the community's views on the current rise of LGBT which can trigger the destruction of the morals of the Indonesian nation. The theory used in this study is the theory of people's views through observations by interviewing several communities and conducting online surveys.